(untitled) (MAUSAM, 1966)
Variations of the height and temperature of tropopause over India have been discussed in this paper. Seasonal and latitudinal variations over India have been compared with those over neighbouring stations. Smith (1963) suggested that increase in moisture contributes to the lowering of the tropopause; but a comparison of the mixing ratios with tropopause heights over India does not seem to bear this out.